ANALISIS MODEL TERAS 3-DIMENSI UNTUK EVALUASI PARAMETER KRITIKALITAS REAKTOR PWR MAJU KELAS 1000 MW - Sembiring, Tagor Malem (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
After the Fukushima accident, the use of passive safety system becomes an important requirement for the nuclear power plant (NPP). The advanced PWR NPP with 1000 MW (electric) class, designed by Westinghouse, AP1000, a reactor with the passive safety features as well as simple and modular. Before selecting a nuclear power plant, there should be an evaluation of the design parameter. One important parameter in criticality safety is core criticality parameters. Main problem in evaluating the core criticality parameters of the AP1000 is that the material composition data SS304 and H2O in the reflector (top and bottom of core) and the diameter of SS304 absorber are not provided. Therefore the objective of this research is to obtain a three-dimensional model of AP1000 core and it can be applied in the evaluation of the core criticality parameters. The calculation results show that the optimum composition of SS304 and H2O in the top and bottom reflector is 50 vol%, respectively, while the diameter of the SS304 absorber is 0.960 cm. Evaluation of the critical boron concentration showed a significant difference to the design value. Although the main cause of this difference is not clear, but it can be proved that the critical boron concentration is very sensitive to the density of UO2. For shutdown reactivity, AP1000 has a large subcriticality margin for one operating cycle. It can be concluded that the proposed 3-imensional core model of AP1000 can be used as a reference for other core parameter calculation or other analytical tools in order to evaluate the AP1000 reactor design.